Du savoir savant au savoir enseigné, analyse de l'exposition des connaissances en cours magistral de physique : une étude de cas - Cécile de Hosson; Adry Manrique; Leslie Regad; Aline Robert
Teaching practices at university level have been the target of a wide range of research over the last two decades. In this paper these practices are considered as objects to be understood before becoming objects to be transformed. This understanding is based on a comparative study involving two university teachers from the same academic discipline (physics) and from the same institution and grade (first-year university) considered within a same teaching environment : the lecture. Favoring a didactic approach conducted through a content analysis and the concept of "proximity", this case study aims to grasp the choices made by the teachers in order to bridge the aimed knowledge and the students. This allows the tracing of the physics' teachers goals and the identification of some of the dimensions of their professional identity. Methodologically speaking two different types of analysis have been conducted in parallel : a multi-category analysis and a lexicometric one. The latter allows statistical analyses on the vocabulary of a corpus thanks to formal reorganizations of the whole transcriptions of the lectures. Our results specify important differences between the two observed teachers. One of the teachers presents an epistemology-based course, revealing an ambition on the meaning and the nature of the physics ; the other one seems more centered on a methodological ambition, in connection with the success in the evaluation.